RED RICE MARKETING STRATEGY IN COMPONG VILLAGE, PITU RIASE DISTRICT, SIDENRENG RAPPANG REGENCY - Hardy Ningsi B; Aksal Mursalat; Astrini Padapi; Muhammad Rais Rahmat Razak (FAKULTAS PERTANIAN UNIVERSITAS BORNEO TARAKAN, 2023)
This research aims to determine the internal factors of red rice farmers in Compong Village, the external factors of red rice farmers in Compong Village, and the marketing strategies of red rice farmers in Compong Village. This research uses qualitative descriptive. The sampling technique is based on specific considerations, namely that the determination of informants is not based on guidelines or population representation, but on the depth of information required. The results of the research show 1) SWOT analysis on the marketing of red rice in Compong village, Pitu Riase subdistrict, Sidenreng Rappang district, is that the strength of the high nutritional content of red rice and a suitable location for farming can be an added value for the product. Weaknesses The low level of public awareness about health can influence consumer interest. Opportunity: There is Huge market potential around Sidenreng Rappang Regency and big cities in South Sulawesi. Threats: Tight competition with similar red rice products from other regions. 2) The marketing strategy in Compong village is an ST (Strengths-Threats) strategy that can be taken by utilizing internal strengths to overcome external threats. One emerging external threat is competition from red rice products in the surrounding area. To overcome this threat, Compong Village can maintain its product excellence by improving the quality of red rice products and expanding its marketing network by collaborating with organic food producers.